Avaliação de impacto ambiental da duplicação da rodovia dos tamoios – trecho planalto: implicações para vegetação - Almeida, Eliane De Lima (2016)
This paper discusses how the EIA was relevant on the decision regarding mitigation of environmental impacts on installation of the Duplication of the Tamoios Highway - stretch Plateau, with the objective of verifying its implications on the local ecosystem, compound by an immeasurable plant biodiversity, located in an area with high ecological significance and big social problems.To discuss the said topic, this thesis analyzed the duplication process of Highway Tamoios, Plateau stretch , linking the cities of São José dos Campos to Paraibuna from São Paulo, being compared to the initial proposal of the project with the final implementation of the road, seeking to know the contributions of procedures for the mitigation of environmental impacts on local biodiversity in relation to removal of vegetation and environmental compensation.